INNV-17. TUMOUR TREATING FIELDS: ACCEPTABLE TO A UK POPULATION?. (5th November 2018) - Brodbelt, Andrew; Williams, Matthew; Thorpe, Antonia; Mills, Samantha; Price, Stephen; Lekka, Elvira; Watts, Colin; Davis, Charles; Jenkinson, Michael
Abstract: BACKGROUND: Tumour treating fields (TTFields) are an innovative anticancer treatment that uses alternating electrical fields to disrupt cell division. In a randomized controlled trial, TTFields significantly improved newly diagnosed Glioblastoma patient survival. The device may be thought to be taxing for patients, with almost constant electrode application and battery use. Methods were explored to reduce cost and examine acceptance. METHODS: Three United Kingdom (UK) centres were offered support for trialing the treatment. Patients with proven MGMT unmethylated glioblastoma, had completed radical chemoradiotherapy, had a performance score > 70, and had social support (for placing the electrodes), where approached. Monthly assessments of compliance and quality of life (QOL) (EORTC BN 20), and quarterly MRIs and tolerability questionnaires were completed. RESULTS: Oncologists in one centre declined to support any use of the device. 8 patients were approached in the other two centres, 5 accepted, and 1 further patient had treatment started elsewhere. A UK politician developed glioblastoma, used the device, and this was followed by positive press reports. Clinicians were trained in the use and interface with the equipment. All patients tolerated the treatment and used for 85% or more. The reason for patient refusal was monthly travelling for compliance checks. Adverse comments related to the mobile battery weight. Two patients had skin irritation, and two found that showering was affected. Four patients have progressed, but maintained stable QOL scores. Two patients have died. CONCLUSIONS: TTFields is well tolerated but requires patient dedication to use the device for at least 18 hours per day and in our pilot access study was acceptable to a UK population. Recent positive press support aided recruitment. A significant reduction in cost is required to allow routine UK use.